Biological mechanisms of infection resistance in tissue engineered blood vessels compared to synthetic expanded polytetrafluoroethylene grafts - Juan Wang, PhD; Shelby K.F. Blalock, BS; Garyn S. Levitan, BS; Heather L. Prichard, PhD; Laura E. Niklason, MD, PhD; Robert D. Kirkton, PhD (JVS - Vascular Science, 2023)
Objective: Synthetic expanded polytetrafluoroethylene (ePTFE) grafts are known to be susceptible to bacterial infection. Results from preclinical and clinical studies of bioengineered human acellular vessels (HAVs) have shown relatively low rates of infection. This study evaluates the interactions of human neutrophils and bacteria with ePTFE and HAV vascular conduits to determine whether there is a correlation between neutrophil-conduit interactions and observed differences of their infectivity in vivo. Methods: A phase III comparative clinical study between investigational HAVs (n = 177) and commercial ePTFE grafts (n = 178) used for hemodialysis access (ClinicalTrials.gov Identifier: NCT02644941) was evaluated for conduit infection rates followed by histological analyses of HAV and ePTFE tissue explants. The clinical histopathology of HAV and ePTFE conduits reported to be infected was compared with immunohistochemistry of explanted materials from a preclinical model of bacterial contamination. Mechanistic in vitro studies were then conducted using isolated human neutrophils seeded directly onto HAV and ePTFE materials to analyze neutrophil viability, morphology, and function. Results: Clinical trial results showed that the HAV had a significantly lower (0.93%; P = .0413) infection rate than that of ePTFE (4.54%). Histological analysis of sections from infected grafts explanted approximately 1 year after implantation revealed gram-positive bacteria near cannulation sites. Immunohistochemistry of HAV and ePTFE implanted in a well-controlled rodent infection model suggested that the ePTFE matrix permitted bacterial infiltration and colonization but may be inaccessible to neutrophils. In the same model, the HAV showed host recellularization and lacked detectable bacteria at the 2-week explant. In vitro results demonstrated that the viability of human neutrophils decreased significantly upon exposure to ePTFE, which was associated with neutrophil elastase release in the absence of bacteria. In contrast, neutrophils exposed to the HAV material retained high viability and native morphology. Cocultures of neutrophils and Staphylococcus aureus on the conduit materials demonstrated that neutrophils were more effective at ensnaring and degrading bacteria on the HAV than on ePTFE. Conclusions: The HAV material seems to demonstrate a resistance to bacterial infection. This infection resistance is likely due to the HAV's native-like material composition, which may be more biocompatible with host neutrophils than synthetic vascular graft material. : Clinical Relevance: Clinical trial results to date have shown that human acellular vessels may be a promising alternative to synthetic conduits in certain indications based on mechanical function, host remodeling, and low infection rates. Resistance to infection may be inherent to the human acellular vessel based on its biological composition, which supports the migration and normal function of a patient's own cells after implantation.